Optical, Electrical and Photocatalytic Properties of the Ternary Semiconductors ZnxCd1-xS, CuxCd1-xS and CuxZn1-xS - Sandra Andrea Mayén-Hernández; David Santos-Cruz; Francisco de Moure-Flores; Sergio Alfonso Pérez-García; Liliana Licea-Jiménez; Ma. Concepción Arenas-Arrocena; José de Jesús Coronel-Hernández; José Santos-Cruz (International Journal of Photoenergy)
The effects of vacuum annealing at different temperatures on the optical, electrical and photocatalytic properties of polycrystalline and amorphous thin films of the ternary semiconductor alloys ZnxCd1-xS, CuxCd1-xS and CuxZn1-xS were investigated in stacks of binary semiconductors obtained by chemical bath deposition. The electrical properties were measured at room temperature using a four-contact probe in the Van der Pauw configuration. The energy band gap of the films varied from 2.30 to 2.85 eV. The photocatalytic activity of the semiconductor thin films was evaluated by the degradation of an aqueous methylene blue solution. The thin film of ZnxCd1-xS annealed under vacuum at 300°C exhibited the highest photocatalytic activity.